ASSESSMENT OF THE DENTAL STATUS IN INDIVIDUALS WITH ALZHEIMER’S DISEASE - Babenia, H.O.; Harashchuk, I.V.; Shnaider, S.A.; Nikolaeva, H.O.; Korniichuk, O.E.; Dieva, T.V.; Diev, Ye.V. (World of Medicine and Biology, 2024)
The work was devoted to the assessment of the condition of hard tissues of teeth and periodontal tissues in people with Alzheimer’s disease. A total of 27 patients with Alzheimer’s disease (62–80 years old) participated in the clinical trials. The study included patients with early or early moderate dementia (disease duration 3–5 years). The patients were assessed for the condition of their hard dental tissues and periodontal tissues. Clinical examination of patients showed that patients with dementia have a greater number of extracted teeth compared to patients of the same age without cognitive impairment, more pronounced atrophic-dystrophic processes in periodontal tissues (100 % gingival recession) and insufficient level of dental care, which justifies the need to develop an integrated approach to maintaining oral health in this category of patients.